The Effect of N-butyl-2-Cyanoacrylate on Wound Healing in the Head and Neck Region - KAPUSUZ, Zeliha; Kenan Dağlıoğlu, Y.; Gencer, Muzaffer; ÖZKIRIŞ, Mahmut; SAYDAM, Levent; Polat, Sait (ENT Updates, 2019)
Objective: The study compares the histological appearances of an induced open wound injury as it heals in rabbits, where healing was assisted by either Batticon (a topical antiseptic solution), or Glubran (a surgical glue). Materials And Methods: The study protocol was first approved by the Research Ethics Committee of Çukurova University. Twenty-eight rabbits with a weight of between 3 and 4kg, of female sex, were subjected to handling every day for a fortnight preceding the experimental injury so that they could be behaviourally assessed. Seven of the 28 rabbits acted as controls, with the 21 others put into one of 3 groups, depending on the day they were to be sacrificed. For the control animals, a portion of the external ear was excised and examined histologically alongside the intervention group animals, to allow comparisons to be made. The intervention group underwent exposure of a 1cm2 area of epidermis bilaterally. The resulting open injury was then treated on one side with topical antisepis using Batticon and on the other with the Glubran tissue glue. At days 2, 4 and 6 post-surgery, the rabbits were sacrificed and sections of the open wound were viewed with the electron microscope. The control group was also examined histologically for comparison. Results: The sections from ears treated with Glubran had electron microscopic appearances indicative of more extensive regeneration than those where Batticon was used at days 2, 4 and 6. Conclusion: The results of the study show that N-butyl-2-cyanoacrylate (Glubran) is suitable for the treatment of open injuries to the head or neck.